OC-041 Management of adult eosinophilic oesophagitis: analysis of medical and dietary outcomes in a uk centre. (17th June 2017) - Hunter, H; Pupinyte, K; Terry, W; Dunn, JM; Toner, E; Zeki, S; Till, SJ; Lomer, MC
Abstract : Introduction: Management of eosinophilic oesophagitis (EoE) includes proton pump inhibitors (PPIs), topical steroids, or dietary intervention. In adults dietary management commonly consists of either the six-food elimination diet (SFED) or allergy-test directed food exclusion. To date patient characteristics and outcomes from various interventions have not been reported in a UK population. Method: A retrospective evaluation of adults (≥16 years) with oesophageal eosinophilia (≥15 eos/hpf) over a two-year period was undertaken. Patients were identified from histology reports and clinical records. Treatment episodes were analysed in those who had both pre- and post-intervention biopsies. Patients who underwent dietary interventions were advised by a specialist dietitian. Results: Our search identified 100 subjects 18–84 years of age (median 35) with a predominance of males (76%; 76/100) and Caucasians (94%; 67/71). Atopic conditions were reported in 75% (65/87) and allergy testing with skin prick or specific IgE tests was positive to food allergens for 71% (44/62) and aeroallergens 72% (38/53). PPIs were given first-line for 75% (38/51) and overall 22% fully responded to a PPI (5/23). Fifty-one patients had both biopsies covering 73 treatment episodes (table 1). Signficant reductions in eosinophil counts were seen for SFED and allergy-test directed diets. There were no significant differences in efficacy between treatment groups. Conclusion: Baseline characteristics were comparable to other described cohorts with a high proportion of males, Caucasians and a high rate of atopy. Dietary intervention particularly with the SFED appears to be effective in our population, with a non-significant trend to higher response rates compared to other interventions. Since the most common triggers were dairy and cereals, empirical exclusion of these two food groups may be an effective approach. Disclosure of Interest: None Declared